Ectoine from Bacterial and Algal Origin Is a Compatible Solute in Microalgae - Simona Fenizia; Kathleen Thume; Marino Wirgenings; Georg Pohnert (Marine Drugs, 2020)
Osmoregulation in phytoplankton is attributed to several highly polar low-molecular-weight metabolites. A widely accepted model considers dimethylsulfoniopropionate (DMSP) as the most important and abundant osmotically active metabolite. Using an optimized procedure for the extraction and detection of highly polar metabolites, we expand the group of phytoplankton osmolytes by identifying ectoine in several microalgae. Ectoine is known as a bacterial compatible solute, but, to the best of our knowledge, was never considered as a phytoplankton-derived product. Given the ability of microalgae to take up zwitterions, such as DMSP, we tested the hypothesis that the algal ectoine is derived from associated bacteria. We therefore analyzed methanol extracts of xenic and axenic cultures of two different species of microalgae and could detect elevated concentrations of ectoine in those that harbor associated bacteria. However, also microalgae without an associated microbiome contain ectoine in smaller amounts, pointing towards a dual origin of this metabolite in the algae from their own biosynthesis as well as from uptake. We also tested the role of ectoine in the osmoadaptation of microalgae. In the model diatoms Thalassiosira weissflogii and Phaeodactylum tricornutum, elevated amounts of ectoine were found when cultivated in seawater with salinities of 50 PSU compared to the standard culture conditions of 35 PSU. Therefore, we add ectoine to the family of osmoadaptive metabolites in phytoplankton and prove a new, potentially synergistic metabolic interplay of bacteria and algae.